Seasonal Changes of Macrophytes in Major Estuaries of Gujarat, India - Mehta, Disha N.; Katara, Ilesh; Kamboj, Ravi D.; Nagar, Padamnabhi S.; Shah, Dharmendra G. (Indian Forester, 2022)
Gulf of Khambhat is the biggest gulf of Western India, having four major rivers i.e., Sabarmati, Mahi, Narmada and Tapi. These estuaries, rich in macrophytes were studied for understanding the change of vegetation pattern across different seasons. Vegetation composition at Sabarmati, Mahi, Narmada and Tapi estuaries was dominated by halophytes Avicennia marina, Acanthus ilicifolius, Aeluropus lagopoides and Suaeda maritima species. The halophyte diversity was predominating over hydrophytes in all the estuaries. There is narrow ecological transition between aquatic and terrestrial species. Avicennia marina showed maximum frequency of occurrence at Sabarmati estuary. Phytosociological analysis was done in order to understand the change in the vegetation pattern wherein at Narmada estuary the abundance of Proteresia coarctata was decreasing from winter to monsoon season while Acanthus ilicifolius and Sonneratia alba were recorded at Tapi estuary only. Maximum value of Shannon's index diversity (SHID) was > 2 to 4 and Simpson diversity index (SIDI) was 0.87 to 0.97 in different seasons across four estuaries. GIS mapping and heterogeneity in the vegetation patches were studied by FRAGSTATS software. Maximum heterogeneity was recorded at Narmada estuary.